The Linguacultural Aspect of the Change of Meaning - Abdusaidova Gulhayo Bahriddin qizi (Genius Journals, 2023)
During the last decades in Uzbekistan important documents aimed at creation of favorable conditions to bring up a new highly educated generation and to support gifted children and the youth were adopted. Among these important documents are: the Laws of the Republic of Uzbekistan – “On the National Program of Personnel training”. On education, the Resolution of the Cabinet of Ministers, “On the organization of general secondary education in Republic of Uzbekistan and others. There are many other opportunities in our country for language learning and teaching. One of the steps to improve English language in secondary schools is the decree declared on December 10, 2012 by the First President of Uzbekistan, Islam Karimov Abduganiyevich. He resolved to improve foreign language leaning system with the decree “On measures to improve further foreign language learning system”. Our first president Islam Karimov said: “The education of the population in the process of the assimilation of ‘world democratic values’ is of primary importance”.
Keywords: The semantic; Lexica-semantic; Lingo cultural features